Monitoring of breath VOCs and electrical impedance tomography under pulmonary recruitment in mechanically ventilated patients. (9th January 2017) - Brock, Beate; Kamysek, Svend; Silz, Josephine; Trefz, Phillip; Schubert, Jochen K; Miekisch, Wolfram
Abstract: Analysis of exhaled VOCs can provide information on physiology, metabolic processes, oxidative stress and lung diseases. In critically ill patients, VOC analysis may be used to gain complimentary information beyond global clinical parameters. This seems especially attractive in mechanically ventilated patients frequently suffering from impairment of gas exchange. This study was intended to assess (a) the effects of recruitment maneuvers onto VOC profiles, (b) the correlations between electrical impedance tomography (EIT) data and VOC profiles and (c) the effects of recruitment onto distribution of ventilation. Eleven mechanically ventilated patients were investigated during lung recruitment after cardiac surgery. Continuous breath gas analysis by means of PTR-ToF-MS, EIT and blood gas analyses were performed simultaneously. More than 300 mass traces could be detected and monitored continuously by means of PTR-ToF-MS in every patient. Exhaled VOC concentrations varied with recruitment induced changes in minute ventilation and cardiac output. Ammonia exhalation depended on blood pH. The improvement in dorsal lung ventilation during recruitment ranged from 9% to 110%. Correlations between exhaled concentrations of acetone, isoprene, benzene sevoflurane and improvement in regional ventilation during recruitment were observed. Extent and quality of these correlations depended on physico-chemical properties of the VOCs. Combination of continuous real-time breath analysis and EIT revealed correlations between exhaled VOC concentrations and distribution of ventilation. This setup enabled immediate recognition of physiological and therapeutic effects in ICU patients. In a perspective, VOC analysis could be used for non-invasive control and optimization of ventilation strategies.